Overexpression of minichromosome maintenance protein 10 in medulloblastoma and its clinical implications. Issue 12 (9th June 2017) - Senfter, Daniel; Erkan, Erdogan Pekcan; Özer, Erdener; Jungwirth, Gerhard; Madlener, Sibylle; Kool, Marcel; Ströbel, Thomas; Saydam, Nurten; Saydam, Okay
Abstract: Background: Overexpression of minichromosome maintenance (MCM) proteins 2, 3, and 7 is associated with migration and invasion in medulloblastoma (MB). However, expression profiling of all prereplication complex (pre‐RC) has not been addressed in MBs. Procedure: We performed mRNA expression profiling of a large set of pre‐RC elements in cell lines and tumor tissues of MB. RNAi technology was employed for functional studies in MB cell lines. Results: Our data showed that most of the pre‐RC components are significantly overexpressed in MB. Among all pre‐RC mRNAs, MCM10 showed the highest level of expression (∼500‐ to 1, 000‐fold) in MB cell lines and tissues compared to the levels detected in cerebellum. In addition, RNAi silencing of MCM10 caused reduced cell proliferation and cell viability in MB cells. Conclusions: Taken together, our study reveals that the pre‐RC is dysregulated in MB. In addition, MCM10, a member of this complex, is significantly overexpressed in MB and is required for tumor cell proliferation.